A study of correlation of clinical scoring (Siriraj stroke score) and ct-scan in patients of stroke. - Dhakal, Mahesh (2000)
ABSTRACT: Objective: TO assess the diagnostic accuracy of Siriraj stroke score with regard to pathological types of stroke in Nepalese sub-population. Design: Validation study of Siriraj stroke score in 100 consecutive patients with acute stroke, computerized brain scans being used for definitive diagnosis. Setting: Tribhuvan University Teaching Hospital, Kathmandu. Subjects: 100 consecutive patients of acute stroke admitted under department of internal medicine through the emergency room. Results: In this validation study of the Siriraj stroke score, the diagnostic sensitivities of the score for haemorrhagic stroke and infarction were 96.15 % and 95.2% respectively, with and overall predictive accuracy of 95.7% when CT brain scanning done within first 72 hours of the onset of stroke was taken as the gold standard. Conclusion: The Siriraj stroke score can be used as a reliable bed side method for diagnosing acute stroke in Nepalese population and for deciding which patients should have priority for computed tomography. It is also a valuable tool for epidemiological studies of stroke incidence and outcome.